Comparative Topographical Description of the Central Nervous System of the Macaw (Ara ararauna) and the Owl (Tyto furcata) - Melo, Luana Felix de; Azarias, Felipe Rici; Walther, Maria Eugenia Furtado; Aquino, Julia Bastos de; Rodrigues, Rosangela Felipe [UNESP]; Melo, Alan Ferraz de [UNESP]; Stapait, Helder Telles; Lopes, Edris Queiroz; Rici, Rose Eli Grassi (Soc Chilena Anatomia, 2022)
The study of animal neurology has historically focused on the closest descendants of humans, such as monkeys and chimpanzees. Because of this, the neurology of birds remains poorly studied and understood by humans compared to other groups of animals. Thus, the objective was to describe the central nervous system to better understand its functioning, correlating the findings with the role it plays in the physiology and biology of birds, comparing species with different behaviors between herbivores and carnivores, filling gaps in the literature serving as subsidy for future research.
Keywords: Birds; Brain; Nervous system